The Effectiveness of Filial Therapy and Cognitive-Behavioral Art-Play on Meta-emotion View of Mothers of Single-parent Children During Coronavirus Quarantine - Nasim Esteki Azad; Mohsen Golparvar; Ilnaz Sajjadian (Gonabad University of Medical Sciences, 2022)
Background: Social distance, linked with negative emotional impacts, is one strategy to avoid COVID-19 disease, particularly for single parents and their children. This research aimed to see how Filial therapy and cognitive-behavioral art-play therapy can help single mothers' emotional perspectives. Methods: A quasi-experimental study was conducted with three groups in two stages: pre-test and post-test. The study's statistical population included mothers of children aged 6 to 12 years living in Isfahan City, Iran, in 1400. A total of 54 mothers with single parent children were chosen via purposive sampling method based on the inclusion criteria. Then, they were randomly assigned to three experimental and control groups during public call in. The dependent variable was measured online using Evelynekehe (2011) meta-emotion perspective questionnaire. In ten consecutive sessions, mothers with children in the two groups received the intervention, whereas the control group received no intervention. Multivariate analysis of covariance was used to analyze the obtained data in SPSS software, v. 27. Results: There was a significant difference in guidance beliefs between the art-play therapy group and the Filial therapy group, as well as between the two modalities of treatment (P<0.01). The findings also revealed a significant difference in views about sufficiency and competence between the art-play and the Filial control group (P<0.01), as well as between the Filial therapy and the control group (P<0.01). This finding suggests that art-play and Filial therapy boosted meta-emotion and its components in Evelynekehe. Conclusion: Considering the effect of two interventions of art - play therapy and filial therapy on improving the mother 's meta-emotion perspective and the effect of art - play therapy on moderating ideas related to guidance and competence of mothers, it is necessary to pay attention to medical and educational planning. Consider the plight of single mothers in the COVID-19 epidemic and quarantine.